Transformasi Digital UMKM: Analisis Pemasaran Online dan Dampaknya terhadap Ekonomi Lokal di Indonesia - Mukhtar Galib; Faridah Faridah; muharram muharram; Thanwain Thanwain (Journal of Economics and Regional Science, 2024)
This research explores the adaptation of MSMEs in Indonesia to digital marketing and its impact on the local economy. Through desk research methods, various literature, data, and previous studies were analyzed to understand the level of digital technology adoption, challenges faced, and adaptation strategies successfully implemented by MSMEs in different local economic contexts. The results show that most MSMEs have adopted digital technologies for marketing activities, with social media, websites and marketplaces being the main platforms. Digitalization is proven to increase MSMEs' market access and income, and contribute positively to local economic growth. However, challenges such as lack of digital skills, consumer trust, and access to capital remain significant obstacles. Successful MSMEs tend to be proactive in learning and adapting, and building consumer trust through good customer service. This research makes a significant contribution to the development of contextualized and inclusive digital marketing theory, and offers practical guidance for MSMEs and policymakers to support sustainable digital transformation in Indonesia